Socio-Cultural Norms and Compliance with Cervical Cancer Screening: A Phenomenological Study among High-Risk Women - Sumiaty Sumiaty; Muhammad Nur Ali; Muhamad Hasan (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Background: Cervical cancer can be prevented through HPV vaccination and screening. However, the screening rate among women in Indonesia is still below 10%. Screening coverage in Palu City in 2024 is still below the national target (90%), reaching only 19.9%. Low compliance with screening is not only due to a lack of knowledge but also to social and cultural norms. This study aims to analyze social and cultural norms in cervical cancer screening compliance among high-risk women in Palu City. Methods: This study uses a naturalistic paradigm approach with a phenomenological research type. The participants in this study were women aged 30-50 years who met the established criteria. Data analysis is carried out through the stages of data reduction, thematic categorization, sociological interpretation, and theoretical synthesis using Durkheim's Collective Conscience theory, Bicchieri's Social Norms Theory, and Health Belief Model Theory. Results: The results of the study suggest that taboo norms are most dominant in cervical cancer screening compliance, with women who undergo reproductive organ examinations being considered shameful and rude. Folkways norms reveal that women only get checked when symptoms appear and self-medicate with traditional remedies. Moral values such as shame or husband's permission weaken the decision to undergo screening. Preventive knowledge and barriers such as stigma, shame, and lack of support weaken screening awareness. Conclusion: In conclusion, cervical cancer screening compliance is a social phenomenon shaped by taboo social norms, morality, customs, and symbolic power roles. Therefore, Socio-Normative Health Awareness Theory is a new intervention concept that reorients social norms into more effective empowerment tools, such as spousal consent, the role of religious leaders, customs, and morality as forces to strengthen awareness and participation in screening.